Multidisciplinary Collaboration of Students in KKN PMM for Sustainable Development in Bukian Village, Payangan District, Gianyar - KURNIAWATI, Ni Putu Ayu Tika; PUTRA, I Wayan Gde Yogiswara Darma; DEWI, Anak Agung Istri Krisna Gangga (PT Keberlanjutan Strategis Indonesia, 2025)
The Regular PMM KKN Program Period II in Bukian Village, Payangan District, Gianyar Regency, Bali, is a form of implementation of the tridharma of higher education through community service based on village potential and problems. Activities carried out by Warmadewa University students include strengthening community capacity in the fields of health (optimization of intergenerational posyandu, integrated health checks, stunting prevention), education (children's financial literacy, bullying prevention, local culture-based pasraman kilat), economy (empowerment of MSMEs through promotional media, development of the Magenda Park tourist village), and environment (making trash sepit, managing organic waste into compost and community service in Magenda Park). Each program is designed in line with the SDGs targets, is promotive and preventive oriented, and is implemented with a participatory approach through the involvement of village officials, posyandu cadres, schools, and the local community. The results of the activities show an increase in collective awareness in health management, strengthening cultural identity, economic literacy, and community participation in protecting the environment. These findings indicate that the success of the KKN program lies not only in the achievement of short-term activities, but also in strengthening the capacity of the community to transform towards independent, competitive, and sustainable village development.